Data from Safety and Efficacy of Tucatinib, Letrozole, and Palbociclib in Patients with Previously Treated HR+/HER2+ Breast Cancer - Elena Shagisultanova; William Gradishar; Ursa Brown-Glaberman; Pavani Chalasani; Andrew J. Brenner; Alison Stopeck; Hannah Parris; Dexiang Gao; Tessa McSpadden; Jose Mayordomo; Jennifer R. Diamond; Peter Kabos; et al. (2023)
AbstractPurpose:To overcome resistance to antihormonal and HER2-targeted agents mediated by cyclin D1-CDK4/6 complex, we proposed an oral combination of the HER2 inhibitor tucatinib, aromatase inhibitor letrozole, and CDK4/6 inhibitor palbociclib (TLP combination) for treatment of HR+/HER2+ metastatic breast cancer (MBC).Patients and Methods:Phase Ib/II TLP trial (NCT03054363) enrolled patients with HR+/HER2+ MBC treated with ≥2 HER2-targeted agents. The phase Ib primary endpoint was safety of the regimen evaluated by NCI CTCAE version 4.3. The phase II primary endpoint was efficacy by median progression-free survival (mPFS).Results:Forty-two women ages 22 to 81 years were enrolled. Patients received a median of two lines of therapy in the metastatic setting, 71.4% had visceral disease, 35.7% had CNS disease. The most common treatment-emergent adverse events (AE) of grade ≥3 were neutropenia (64.3%), leukopenia (23.8%), diarrhea (19.0%), and fatigue (14.3%). Tucatinib increased AUC10–19 hours of palbociclib 1.7-fold, requiring palbociclib dose reduction from 125 to 75 mg daily. In 40 response-evaluable patients, mPFS was 8.4 months, with similar mPFS in non-CNS and CNS cohorts (10.0 months vs. 8.2 months; P = 0.9). Overall response rate was 44.5%, median duration of response was 13.9 months, and clinical benefit rate was 70.4%; 60% of patients were on treatment for ≥6 months, 25% for ≥1 year, and 10% for ≥2 years. In the CNS cohort, 26.6% of patients remained on study for ≥1 year.Conclusions:TLP combination was safe and tolerable. AEs were expected and manageable with supportive therapy and dose reductions. TLP showed excellent efficacy for an all-oral chemotherapy-free regimen warranting further testing.See related commentary by Huppert and Rugo, p. 4993